Vascular‐targeted nanocarriers: design considerations and strategies for successful treatment of atherosclerosis and other vascular diseases. (19th May 2016) - Kelley, William J.; Safari, Hanieh; Lopez‐Cazares, Genesis; Eniola‐Adefeso, Omolola
Abstract : Vascular‐targeted nanocarriers are an attractive option for the treatment of a number of cardiovascular diseases, as they allow for more specific delivery and increased efficacy of many small molecule drugs. However, immune clearance, limited cellular uptake, and particle‐cell dynamics in blood flow can hinder nanocarrier efficacy in many applications. This review aims to investigate successful strategies for the use of vascular‐targeted nanocarriers in the treatment of cardiovascular diseases such as atherosclerosis. In particular, the review will highlight strategies employed for actively targeting the components of the atherosclerotic plaque, including endothelial cells, macrophages, and platelets and passive targeting via endothelial permeability, as well as design specifications (such as size, shape, and density) aimed at enhancing the ability of nanocarriers to reach the vascular wall. WIREs Nanomed Nanobiotechnol 2016, 8:909–926. doi: 10.1002/wnan.1414 This article is categorized under: Therapeutic Approaches and Drug Discovery > Nanomedicine for Cardiovascular Disease Therapeutic Approaches and Drug Discovery > Nanomedicine for Neurological Disease Nanotechnology Approaches to Biology > Nanoscale Systems in Biology